PENGEMBANGAN MEDIA PPT ANIMASI SIKLUS KATAK SEKOLAH DASAR - Abdul Nazidiq; Yusni Arni; Dzaky Alfikri; Muhammad Alfizar (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
The speed of development of science and technology indicates changes in teaching methods and strategies. A teacher is perhaps one of the most important learning resources who can impart all knowledge and information to a child. Instructors encourage students to understand facts and information on their own and help them develop them. Therefore, there is a need for initiatives to improve the quality of education by reducing the role of teachers as sources of information (teacher centric). The development model used in this research is Research and Development (R&D) which involves creating educational media such as animated educational videos to increase students' interest in learning. The aim of PowerPoint-based learning materials is to help students understand the stages of frog development visually and interactively. For example, looking at the life cycle of frogs, such as eggs, tadpoles, young frogs, and even adult frogs, helps students understand concepts more clearly. Based on the research that has been conducted, it is known that the learning goals of elementary school students have not been achieved because their learning motivation is very low. Therefore, researchers are motivated to conduct research on the development of educational media because this media can provide interesting educational content and can encourage students to participate in the learning process. It is important to consider quality and criteria when developing research. Evaluate product quality by paying attention to the criteria of validity, effectiveness, practicality and attractiveness.